Multi-channel microelectrode arrays for detection of single-cell level neural information in the hippocampus CA1 under general anesthesia induced by low-dose isoflurane - Ruilin Hu; Penghui Fan; Yiding Wang; Jin Shan; Luyi Jing; Wei Xu; Fan Mo; Mixia Wang; Yan Luo; Ying Wang; Xinxia Cai; Jinping Luo (Fundamental Research)
Timely monitoring of anesthesia status during surgery is important to prevent an overdose of isoflurane anesthesia. Therefore, in-depth studies of the neural mechanisms of anesthetics are warranted. Hippocampal CA1 plays an important role during anesthesia. Currently, a high spatiotemporal resolution microdevice technology for the accurate detection of deep brain nuclei is lacking. In this research, four-shank 32-channel implantable microelectrode arrays (MEAs) were developed for the real-time recording of single-cell level neural information in rat hippocampal CA1. Platinum nanoparticles were modified onto the microelectrodes to substantially enhance the electrical properties of the microelectrode arrays. The modified MEAs exhibited low impedance (11.5 ± 1 kΩ) and small phase delay (-18.5° ± 2.54°), which enabled the MEAs to record single-cell level neural information with a high signal-to-noise ratio. The MEAs were implanted into the CA1 nuclei of the anesthetized rats, and the electrophysiological signals were recorded under different degrees of anesthesia mediated by low-dose concentrations of isoflurane. The recorded signals were analyzed in depth. Isoflurane caused an inhibition of spike firing rate in hippocampal CA1 neurons, while inducing low-frequency oscillations in CA1, thus enhancing the low-frequency power of local field potentials. In this manner, the spike firing rate and the power of local field potentials in CA1 could characterize the degree of isoflurane anesthesia. The present study provides a technical tool to study the neural mechanisms of isoflurane anesthesia and a research method for monitoring the depth of isoflurane anesthesia in clinical practice.